Measuring the Innovativeness of Economy Using Direct and Indirect Innovation Indicators - Geodecki, Tomasz (Journal of Public Governance, 2018)
The article deals with the issues related to measuring the innovativeness of an economy. Parts one and two outline the contexts and premises behind the application of certain approaches to such measurement and present crucial indicators based on the measurement of R&D activity and its effects as well as direct indicators of innovation. Part three sketches the perspective and criteria for the evaluation of these coefficients; parts four and five analyse these measures from pointing terms of their applicability to comparisons of innovativeness of economies. The discussion thereafter focuses on the limited usefulness of indirect indicators to the estimation of innovativeness of developing countries.